Data Collection İn Wireless Sensor Network Through Hybrid Mac Protocol - Dr.A.Vanitha, Dr.N.Balakrishnan (International Journal of Advanced Science and Technology, 2020)
A Wireless Sensor Network (WSN) usually refers to a cluster of spatially distributed and allocated sensors to observe and record the physical parameters of the surroundings and have the ability to organize the gathered data into a significant location. The network that arranges an unmanned aerial vehicle (UAV) basically for collection of data totally differs from the standard WSN architecture. In UAV based WSN, limited time is allocated to the sensor nodes for communication with the UAV, which causes transmission of information to the UAV in a short period of time. The impartiality between the contended nodes is corrupted that in directly affects the performance of the network in terms of throughput and ration of data packet delivery. To overcome the aforementioned issue, in this paper an operational protocol is discloses that has the ability to maintain or upsurge the fairness between the nodes. The proposed protocol is a hybrid medium access protocol (MAC) to collect information in the UAV based wireless network